Validation of the Chemotaxis of Plant Parasitic Nematodes Toward Host Root Exudates - Liu, Wenshan; Jones, Alexis L.; Gosse, Heather N.; Lawrence, Kathy S.; Park, Sang-Wook (Journal of nematology, 2019)
Plant parasitic nematodes (PPN) are microscopic soil herbivores that cause damage to many economic crops. For the last century, it has been proposed that chemotaxis is the primary means by which PPN locate host plant roots. The identities and modes of action of chemoattractants that deliver host-specific messages to PPN, however, are still elusive. In this study, a unique multidimensional agar-based motility assay was developed to assess the impacts of root exudates on the short-range motility and orientation of PPN. Three PPN ( , and ) and root exudates from their respective host and non-host plants (cotton, soybean, and peanut) were used to validate the assay. As predicted, and were attracted to root exudates of cotton and soybean (hosts), but not to the exudates of peanut (non-host). Likewise, was attracted to soybean (host) root exudates. These results underpinned the intrinsic roles of root exudates in conveying the host specificity of PPN. In particular, PPN selectively identified and targeted to hydrophilic, but not hydrophobic, fractions of root exudates, indicating that groundwater should be an effective matrix for chemotaxis associated with PPN and their host plant interactions.